2013
DOI: 10.1044/cicsd_40_f_116
|View full text |Cite
|
Sign up to set email alerts
|

Academic Training of Audiology Graduate Students in Vestibular Evaluation and Balance Assessment Procedures

Abstract: The aim of this study was to obtain information regarding the vestibular evaluation and balance assessment coursework and clinical practicum of audiology graduate training programs across the United States. The students' anticipated competency levels for performing various vestibular/balance procedures, along with their anticipated confidence levels in interpreting the tests, were reviewed. A database of audiology graduate programs was constructed to present information regarding the course/lab components and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…One study from the USA, identified that very few audiology doctoral programs incorporated fall risk assessment training into the vestibular and balance coursework, with only 40% of the students reporting hands on experience with fall risk assessments (Callahan et al, 2013). This finding corresponds with findings in a later dissertation which revealed that only 19% of audiologists felt their university coursework prepared them to conduct fall-risk assessment measures (Bassett, 2018).…”
Section: Poor Remunerationmentioning
confidence: 83%
See 2 more Smart Citations
“…One study from the USA, identified that very few audiology doctoral programs incorporated fall risk assessment training into the vestibular and balance coursework, with only 40% of the students reporting hands on experience with fall risk assessments (Callahan et al, 2013). This finding corresponds with findings in a later dissertation which revealed that only 19% of audiologists felt their university coursework prepared them to conduct fall-risk assessment measures (Bassett, 2018).…”
Section: Poor Remunerationmentioning
confidence: 83%
“…Several authors have expressed the sentiment that there is a need for further training in fall-risk practice through improved graduate coursework or continuing education credits (Bassett & Honaker, 2016;Callahan et al, 2013;Criter & Honaker, 2017), with the suggestion that it should perhaps be introduced at the same time hearing assessment is being taught and practiced (Jedlicka, 2020).…”
Section: Poor Remunerationmentioning
confidence: 99%
See 1 more Smart Citation
“…ecently, I stumbled over an article that was published in Contemporary Issues in Communication Science and Disorders titled, "Academic training of audiology graduate students in vestibular evaluation and balance assessment procedures." The article was written by Callahan et al (2013) and represented the result of a survey conducted by the investigators describing, in some detail, the level of preparation of students graduating from Au.D. programs.…”
mentioning
confidence: 99%